Exploring the Internet of Behavior : Key Examples and Insights - Kumar, S. Ashok; Sripriya, P. V. (Indian Journal of Computer Science, 2024)
The Internet of Behavior (IoB) is emerging as a ground breaking concept in the digital landscape extending the capabilities of the Internet of Things (IoT) to analyze and influence human behavior. It aims to explore key internet of behavior examples and provides insights into its evolving ecosystem. The present paper will delve into the evolution of IoB, examine data collection methods, and discuss the role of machine learning in processing behavioral data. The paper will also investigate the applications in personal health and business contexts, address the regulatory landscape, and highlight cyber security concerns.